Posttransplant Erythrocytosis after Allogenic Stem Cell Transplant for Acute Myeloid Leukemia: A Case Report and Review of Literature - Sherry S. Abraham; Saikumar Soman; Akshaya B. Ajish; Sreejith G. Nair (Indian Journal of Medical and Paediatric Oncology)
Postallogenic hematopoietic stem cell transplant (post-allo-HSCT) erythrocytosis is a rare phenomenon mostly seen in cases of aplastic anemia. It is a well-known complication in renal transplant recipients. Clinical evaluation, serum erythropoietin (EPO) level, and Janus kinase 2 (JAK 2) mutation are important to differentiate between primary and secondary erythrocytoses. Treatment aims at normalizing the clinical, physical, and laboratory parameters and minimizing thromboembolic complications. The majority of the patients have a favorable outcome with phlebotomies and low-dose aspirin. We report a rare case of post-allo-HSCT erythrocytosis in a patient who underwent related allo-HSCT for acute myeloid leukemia.